2017
DOI: 10.1039/c7cp03484a
|View full text |Cite
|
Sign up to set email alerts
|

A global method for handling fluorescence spectra at high concentration derived from the competition between emission and absorption of colloidal CdTe quantum dots

Abstract: We investigate the effects of the concentration of CdTe quantum dots (QDs) on their fluorescence in water. The emission spectra, acquired in right angle geometry, exhibit highly variable shapes. The measurements evidence a critical value of the concentration beyond which the intensity and the spectral bandwidth decrease and the fluorescence maximum is redshifted. To account for these observations, we develop a model based on the primary and secondary inner filter effects. The accuracy of the model ensures that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…2 molecules, these ligands ensure that QDs are mainly trap-free and do not experience charge transfer, given the insulating nature of the ligand chains, unlike π-conjugated ligands 39,65 . This point is even corroborated by our previous photoluminescence measurements, which showed that these QDs do not suffer from fluorescence quenching, despite their conjugation with short ligands 59 . Henceforth, we do not expect the coupling observed with 2C-SFG spectroscopy to be based on the same mechanisms than those which describe ligand-dependent optoelectronic properties of the core.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…2 molecules, these ligands ensure that QDs are mainly trap-free and do not experience charge transfer, given the insulating nature of the ligand chains, unlike π-conjugated ligands 39,65 . This point is even corroborated by our previous photoluminescence measurements, which showed that these QDs do not suffer from fluorescence quenching, despite their conjugation with short ligands 59 . Henceforth, we do not expect the coupling observed with 2C-SFG spectroscopy to be based on the same mechanisms than those which describe ligand-dependent optoelectronic properties of the core.…”
supporting
confidence: 83%
“…This structure has indeed been characterized by high resolution transmission electron microscopy in ref. 59 . In addition, as discussed in Supplementary Note 1, the value x = 0.25 is compatible with our UV-visible measurements.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of agglomerates at high concentration of QDs could lead to inner filter effects which could eventually redshift the maximum fluorescence wavelength . However, the evolution of UV‐visible spectra in Figure b shows that there is no significant variation of the QDs extinction in the vicinity of 520 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, as depicted in Figure c, DLS measurements evidence over the time the emergence of larger and larger scattering centers. Indeed, aggregates with hydrodynamic radii up to 300 nm are detected at the end of the activation step whereas colloidal CdTe QDs size is initially evaluated at 3.4 nm (which corresponds to previous HR‐TEM analysis wherein the size distribution of identical CdTe QDs was estimated at 3.4±0.6 nm). In addition, the slight decrease of the absorbance at 488 nm (Figure b) is likely to translate a sedimentation of the QDs, here again compatible with the hypothesis of an aggregation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation